Integrating cultural heritage into product design: a leather handbag inspired by Bajang Ratu Temple - Galuh Puspita Sari; Ulfah Nafi'ah; Yuafni; Sugiyanto; Eksihtya Lailatul Mauludina (Industrial Innovation, 2025)
Handbag design serves not only as a fashion accessory but also as a medium for cultural preservation. This paper discusses the design process of a leather handbag inspired by the visual heritage of Bajang Ratu Temple in Mojokerto, a historical site from the Majapahit Kingdom renowned for its architectural and symbolic values. The primary objective of this research is to create a fashion product that integrates traditional aesthetics with contemporary functionality, while also fostering public appreciation of local cultural heritage. The study adopts a creative design methodology, employing data collection through literature review, visual observation, form and ornament analysis, as well as material and production technique exploration. The design outcome demonstrates the integration of distinctive elements of Bajang Ratu Temple, such as the paduraksa gate form and geometric structures, which are transformed into handbag features. The final product takes the form of a prototype that can be further replicated by practitioners in the fashion and leathercraft industries. This research highlights that the integration of product design and local cultural heritage can generate innovative and economically valuable outcomes, while contributing to the preservation of Indonesia’s cultural identity.